International Conference on Snap Beans in the Developing World. Cali, Colombia, 1989. Proceedings (International Center for Tropical Agriculture, 1990)
Reports on snap beans in developing countries are presented, to evaluate restrictions affecting production; directions for future research are also identified. Information presented includes producing regions and production statistics; nutritive value; consumption, marketing, and foreign trade; processing; identification of diseases and pests and of strategies for their control; plant breeding; seed production; socio-economic aspects; and progress in international snap bean research. (CIAT)